Hubungan Mutu Pelayanan dengan Kepuasan Pasien di FDC Dental Klinik Rawamangun - Asep Barkah; Alma Nurmalia (Universitas Malahayati, 2026)
ABSTRACT The quality of healthcare services is a crucial factor influencing patient satisfaction. This study aims to analyze the relationship between the quality of nursing care services and patient satisfaction at FDC Dental Clinic Rawamangun in 2025. This research employed a quantitative method with a correlational design and a cross-sectional approach. A total of 50 respondents were selected using purposive sampling with inclusion criteria of patients aged over 17 years who had received nursing care services at FDC Dental Clinic. Data were collected using a Likert-scale questionnaire measuring service quality based on the five SERVQUAL dimensions (tangible, reliability, responsiveness, assurance, and empathy) and patient satisfaction levels. Data were analyzed univariately and bivariately using the Chi-Square test. The results showed that most patients assessed the quality of care as good (64%), while the majority expressed satisfaction with the services received (70%). The Chi-Square test yielded a p-value of 0.014 ( 0.05), indicating a significant relationship between service quality and patient satisfaction at FDC Dental Clinic Rawamangun. These findings suggest that the better the quality of care provided, the higher the level of patient satisfaction. Keywords: Service Quality, Patient Satisfaction, Nursing Care, FDC Dental Clinic. ABSTRAK Mutu pelayanan kesehatan merupakan faktor penting yang memengaruhi tingkat kepuasan pasien. Penelitian ini bertujuan untuk menganalisis hubungan antara mutu pelayanan perawatan dengan kepuasan pasien di FDC Dental Klinik Rawamangun tahun 2025. Penelitian menggunakan metode kuantitatif dengan desain korelasional dan pendekatan cross sectional. Sampel penelitian berjumlah 50 responden yang dipilih melalui teknik purposive samplingdengan kriteria inklusi pasien berusia di atas 17 tahun serta pernah mendapatkan pelayanan perawatan di FDC Dental Klinik. Instrumen penelitian berupa kuesioner dengan skala Likert yang mengukur mutu pelayanan berdasarkan lima dimensi SERVQUAL (tangible, reliability, responsiveness, assurance, dan empathy) serta tingkat kepuasan pasien. Analisis data dilakukan secara univariat dan bivariat dengan uji Chi-Square.Hasil penelitian menunjukkan bahwa sebagian besar pasien menilai mutu pelayanan dalam kategori baik (64%), sedangkan tingkat kepuasan pasien mayoritas berada pada kategori puas (70%). Hasil uji Chi-Square memperoleh nilai p = 0,014 ( 0,05), yang berarti terdapat hubungan signifikan antara mutu pelayanan perawatan dengan kepuasan pasien di FDC Dental Klinik Rawamangun. Temuan ini mengindikasikan bahwa semakin baik mutu pelayanan yang diberikan, semakin tinggi tingkat kepuasan pasien. Kata Kunci: Mutu Pelayanan, Kepuasan Pasien, Perawatan, FDC Dental Klinik.